Combination free replacement and pro-rata warranty policy optimization model - Stamenković, Dragan D (Journal of Applied Engineering Science, 2011)
Product development risk increases more and more every day. One of the factors that affect this risk is product warranty. Warranty is a powerful marketing instrument for the manufacturer and a good protection for both the manufacturer and the customer, but it always involves additional costs to the manufacturer. These costs depend on the product reliability and the warranty parameters. This paper deals with the optimization of these parameters for known product failure distribution to reduce the warranty costs to the manufacturer while retaining the promotional function of the warranty. Combination free replacement and pro-rata warranty policy is chosen as a model and the length of free replacement and pro-rata policy periods are varied, as well as the coefficients that define the pro-rata cost function. Warranty costs are obtained by using analytical equations and by simulation. The obtained results are shown and discussed and some concluding remarks are given.